2020
DOI: 10.1111/sms.13648
|View full text |Cite
|
Sign up to set email alerts
|

Recording injuries only during winter competitive season underestimates injury incidence in elite alpine skiers

Abstract: Current epidemiological studies in elite alpine skiers are mostly limited to retrospective surveys on in‐season injury. The aim of this study was to determine the risk and pattern of injury in elite alpine skiers during the winter competitive season (WCS) and the summer off‐season (SOS). European Cup skiers were prospectively followed during 5 complete years. A total of 133 skier‐seasons (79 males and 54 females) completed the study. All acute and overuse injuries that required medical attention were registere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 34 publications
(101 reference statements)
2
46
3
Order By: Relevance
“…Despite these plausible sports-related adverse loading patterns, only a few studies, however, have investigated the occurrence of lower back complaints in competitive alpine skiers. Moreover, due to focusing on a different age group and reporting other time prevalence measures or absolute injury rates, most of them are not directly comparable to the results of the current study [3,4,6,8,11]. The only study directly comparable to our investigation reported similar magnitudes of current low back pain (67.0%) in ski high school athletes aged 15-19 years [30].…”
Section: Prevalence Of Lower Back Complaints With Respect To Sex Catcontrasting
confidence: 69%
See 1 more Smart Citation
“…Despite these plausible sports-related adverse loading patterns, only a few studies, however, have investigated the occurrence of lower back complaints in competitive alpine skiers. Moreover, due to focusing on a different age group and reporting other time prevalence measures or absolute injury rates, most of them are not directly comparable to the results of the current study [3,4,6,8,11]. The only study directly comparable to our investigation reported similar magnitudes of current low back pain (67.0%) in ski high school athletes aged 15-19 years [30].…”
Section: Prevalence Of Lower Back Complaints With Respect To Sex Catcontrasting
confidence: 69%
“…Competitive alpine skiing is a popular yet high-risk sport. At all competition levels, health problems are frequent [1][2][3][4][5][6][7]. In particular, lower back has been reported to be one of the most affected body regions for overuse complaints [8].…”
Section: Introductionmentioning
confidence: 99%
“…High prevalence of overuse-related injuries during the offseason preparation period Overall, our data further highlight the remarkably frequent occurrence of overuse injuries in alpine skiers during the off-season preparation period, and the necessity to record injuries during the entire year to avoid a significant underestimation of the actual injury extent. 9 During this particular period, intensive physical conditioning combined with extensive amounts of on-snow training are typical. 12 In contrast, during the competition period, training intensities are much lower (physical preservation training) and skiing is more quality than quantity orientated (only 2-3 runs a day).…”
Section: Open Accessmentioning
confidence: 99%
“…The anatomical regions particularly prone to overuse injuries in skiers are the knee, the hip and the back. [9][10][11] For such patterns, an accumulation of heavy mechanical loads on the musculoskeletal system during intense/ extensive training periods, such as during the aforementioned off-season preparation period, may play an important role. So far lacking, however, is knowledge about the association of overuse injuries and the total training hours, as an estimator of the accumulated overall load caused by off-snow and on-snow training.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation